2014
DOI: 10.5742/mewfm.2014.92558
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s Satisfaction : Insight into Access to Service , Interpersonal Communication and Quality of Care Issues

Abstract: Objective: To assess patient satisfaction and expectations from the family medicine department at a newly established public sector hospital in Riyadh. Methodology: A cross sectional study. Pre tested, pre designed, well structured questionnaire written in English with Arabic translation was administered to randomly selected volunteer patients, who presented to family medicine clinics of a tertiary care hospital from February to March 2014. A total of 148 anonymously completed questionnaires were returned to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…This study achieved a response rate of 96.6%. This is significantly higher than the majority of similar studies 31–33. A study done34 in rural Bengal had a 93.5% response rate.…”
Section: Discussioncontrasting
confidence: 58%
“…This study achieved a response rate of 96.6%. This is significantly higher than the majority of similar studies 31–33. A study done34 in rural Bengal had a 93.5% response rate.…”
Section: Discussioncontrasting
confidence: 58%
“…Studies show that patient satisfaction and participation improved when they perceive that healthcare providers’ communication behaviours are positive (Clever et al . , Al Odhayani & Khawaja , Azizam & Shamsuddin ). Our findings appeared similar to the findings in one of the studies reviewed by Greenfield and Braithwaite () showing that there is need for doctors to improve interpersonal skills, access, availability and patient information.…”
Section: Discussionmentioning
confidence: 97%
“…The results suggest that there is a need for healthcare providers to provide needed information consistently so that patients may be able to make decisions and participate in their therapeutic management. Studies show that patient satisfaction and participation improved when they perceive that healthcare providers' communication behaviours are positive (Clever et al 2008, Al Odhayani & Khawaja 2014, Azizam & Shamsuddin 2015. Our findings appeared similar to the findings in one of the studies reviewed by Greenfield and Braithwaite (2008) showing that there is need for doctors to improve interpersonal skills, access, availability and patient information.…”
Section: Process (Overall) Outcomementioning
confidence: 99%
“…Regarding managerial support, it is shown that perceived supervisor support positively influences patient experience through perceived organizational support and advocacy for employees [28]. Patient Experience and PHC in KSA Locally, the importance of practitioner-patient interaction and its influence on the care experience has been highlighted in the study) [29]. Also, [30] found that a patient's trust in a PHC is strongly associated with effective and clear communication between a patient and Physician.…”
Section: Patient Experience Internationallymentioning
confidence: 96%